Caring for Persons With Intellectual Disabilities and Challenging Behavior: Staff Experiences With a Web-Based Training Program - Truong, Anh; Alverbratt, Catrin; Ekström-Bergström, Anette; Antonsson, Helena (Frontiers in Psychiatry, 2021)
Abstract Background: Clear and effective communication is a prerequisite to provide help and support in healthcare situations, especially in health and social care services for persons with intellectual disabilities, as these clients commonly experience communication difficulties. Knowledge about how to communicate effectively is integral to ensuring the quality of care. Currently, however, there is a lack of such knowledge among staff working in the disabilities sector, which is exacerbated by challenges in the competence provision in municipal health and social care services. Therefore, the aim of the study was to explore staffs’ experience of web-based training in relation to their professional caring for persons with intellectual disabilities and challenging behavior. The intention is to move toward well-evaluated and proven web-based training in order to contribute to competence provision in this specific context. Methods: Fourteen semi-structured interviews were carried out with individual staff members to gather data regarding their experiences with web-based training in relation to their profession. The collected data were analyzed using qualitative content analysis with a focus on both manifest and latent content. Results: The staff’s experiences with the web-based training program were presented as a single main theme: “Web-based training for staff initiates a workplace learning process by promoting reflections on and awareness of how to better care for persons with intellectual disabilities and challenging behavior.” This theme contained three categories which are based on eight sub-categories. Conclusion and clinical implications: The benefits of web-based training for workplace learning could clearly be observed in the strengthening of professional care for persons with intellectual disabilities and challenging behavior. Staff members claimed to have gained novel insights about how to better care for clients as well as about the importance of interactions in their encounters with clients. Professional teamwork is crucial to providing effective care for persons with intellectual disabilities and challenging behavior. Hence, future research aimed at investigating the views of other healthcare professionals, such as registered nurses, is recommended to improve the competence provision within municipal health and social care services and thereby enhance the quality of care.